Uganda - Promoting Inclusive Growth : Transforming Farms, Human Capital, and Economic Geography, Synthesis Report - World Bank (Washington, DC, 2013)
At an average above 6.0 percent per year over the past two decades, Uganda' s growth rate was impressive by all standards. In parallel, poverty declined significantly, not only in urban areas, but also to some extent within the rural areas. This combination was possible because the key drivers of growth were labor-intensive services sectors, some of which are agriculture based. In fact, Uganda's growth process has reduced overall poverty faster than what has been observed in many other developing countries. This report addresses the issue from a double perspective: sectoral and geographical. From a sectoral perspective, it concludes that the agricultural sector needs transformation because it remains the primary employer; it is the country's main comparative advantage and bedrock for industrialization. More broadly, identifying sectors with potential will be important for employment opportunities, which in turn will be largely dependent on productivity levels and thus on the level of education and skills of the labor force. From a geographical perspective, transformation generally yields a concentration of economic activities that leaves some locations lagging in prosperity. This unbalanced growth needs to be supported with appropriate economic integration policies that have been analyzed in the report.